2018
DOI: 10.1038/s41598-018-21912-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intention to obtain the HPV vaccine in South East Asian and Western Pacific regions: A systematic review and meta-analysis

Abstract: Since licensing in 2006, there has been poor uptake of the HPV vaccine among the targeted population in the South East Asia Region (SEAR) and Western Pacific Region (WPR). A systematic review was conducted to identify the studies exploring the relationship between factors and intention for HPV vaccination among women in SEAR and WPR countries. Nineteen studies were identified as suitable for qualitative synthesis, and three as suitable for meta-analysis. Most women had a positive intention to have an HPV vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 42 publications
(182 reference statements)
4
34
0
Order By: Relevance
“…Other studies among university students in other countries have reported similar findings, showing that women had a higher intention of receiving the vaccine than men [ 18 , 26 , 27 ]. The data reported here are consistent with earlier studies, which found an association between a higher knowledge of HPV and its vaccines and the intention to receive the vaccine [ 18 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies among university students in other countries have reported similar findings, showing that women had a higher intention of receiving the vaccine than men [ 18 , 26 , 27 ]. The data reported here are consistent with earlier studies, which found an association between a higher knowledge of HPV and its vaccines and the intention to receive the vaccine [ 18 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Globally, the United States was among the first countries to introduce a HPV immunization program funded by the Government. [7] The Advisory Committee on Immunization Practices of the Centers for Disease Control and Prevention (CDC) recommended the provision of HPV vaccine (3 doses completion) for girls aged 11 or 12 years, and for females aged 13 through 26 years who were not previously vaccinated. ACIP expanded its recommendation in 2011 to include boys as well into the program get the vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…When the HPV vaccine is fully included in the Immunization Program in India, uptake of the vaccine among eligible girls might be low due to misperceptions about HPV infection, cervical cancer and HPV vaccine, or vaccination in general [15][16][17][18]. Lower intention to HPV vaccination was associated with parental negative beliefs about HPV vaccine (e.g.…”
Section: Introductionmentioning
confidence: 99%